2013
DOI: 10.1177/0300060512474567
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking delays in patients with acute myocardial infarction and use of the emergency medical service

Abstract: Objectives: To investigate treatment-seeking delays in Chinese patients with acute myocardial infarction (AMI) and to compare sex differences in this behaviour. Methods: A descriptive cross-sectional study was undertaken in patients with AMI, admitted to one of three hospitals in Shanghai, China. A treatment-seeking behaviour questionnaire was administered to each patient within 48 h of hospital admission. Results: In total, 250 patients were included: 159 men and 91 women. The median time for patients with AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 17 publications
3
25
1
3
Order By: Relevance
“…In addition, we found that women were more likely to delay to seeking medical care after the onset of symptoms suggestive of AMI compared with men. This finding is consistent with worldwide data [23], [24], [25] as well as in a recent survey among patients hospitalized with AMI in China [26]. Public educational interventions for general population are needed to encourage patients to seek medical care promptly to maximize the benefits of currently available treatments.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found that women were more likely to delay to seeking medical care after the onset of symptoms suggestive of AMI compared with men. This finding is consistent with worldwide data [23], [24], [25] as well as in a recent survey among patients hospitalized with AMI in China [26]. Public educational interventions for general population are needed to encourage patients to seek medical care promptly to maximize the benefits of currently available treatments.…”
Section: Discussionsupporting
confidence: 89%
“…While much success has been achieved in reducing the components of delay once a patient enters the health care system, little has changed in treatment-seeking delay times for women. This behavior is universal across cultures including women in Saudi Arabia, 233 China 234 , Brazil 235 , and Norway 236 and across racial groups, including African American women. 237 Recent studies continue to demonstrate that treatment seeking delay is associated with worse outcomes.…”
Section: How Women Experience Ischemic Heart Diseasementioning
confidence: 99%
“…Kinijoje atliktame tyrime nustatyta, jog ilgiau nei 1 valandą delsė 70,8 proc. [14], Graikijoje -82 proc. [13] tiriamųjų, Amerikoje mažiau nei 10 proc.…”
Section: Gs -Galimybių Santykis; Pi -Pasikliautinasis Intervalas; MI unclassified
“…[13], Kinijoje 130 (50 -480) min. [14], Airijoje, vertinant visus ūminius koronarinius sindromus, 244 min [16]. ASSENT-3 PLUS tyrimas parodė, jog kai kuriose šalyse šio laiko mediana trumpesnė: 60 min.…”
Section: Gs -Galimybių Santykis; Pi -Pasikliautinasis Intervalas; MI unclassified